MAPPING STUDIES ON GOOD GOVERNANCE AND E-GOVERNMENT IN DEVELOPING COUNTRIES: A BIBLIOMETRIC REVIEW - Resky Nur Fadillah; Muliana (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal